The Effect of Thermal Insulation on Cooling Load in Residential Buildings in Makkah, Saudi Arabia (Future Cities and Environment, 2020)
Buildings consume huge amounts of electrical energy in the Kingdom of Saudi Arabia, particularly during the summer months, due to the enormous air conditioning demands created by very hot outdoor temperatures. Residential buildings consume more than half of the electricity used in Saudi Arabia, with the air conditioning load making up 70% of this use. The main aim of this study is to evaluate the thermal performance of two mid-rise residential buildings in Makkah, Saudi Arabia. These buildings are five floors in height and have the same orientation, but the first building is thermally insulated, while the second building is not. To investigate the indoor thermal performance of the two buildings, physical measurements were taken during May 2019. The data gathered included indoor air temperature values as recorded every fifteen minutes for a period of sixty-eight hours in two equivalent rooms in each building. Analysis of site monitoring data was conducted, and the results obtained offer a better idea of the effectiveness of the existing building fabric characteristics, in particular external walls and rooves, in relation to indoor thermal performance. These data were calibrated with simulated results taken from thermal analysis software (TAS) to validate them and to thus quantify the cooling load in the case study buildings. The outcomes illustrate the similarity between the measured and simulated results and as well as indicating that thermal insulation can decrease cooling loads by to up to 50%.